Tarqiyatu Itqan Mufradat al-'Arabiyyah bil-Madah al-Ta'limiyyah al-Mu'tamidah 'ala Wasilah al-Sam'iyyah al-Basariyyah VCD fi al-Shaf al-Sabi' bil-Madrasah al-Tsanawiyyah al-Dakhiliyyah Muhammadiyah Palopo - Tosimpak, Hasanuddin; Mardi Takwim; Aisyah Arjuna (Al Ibrah: Journal of Arabic Language Education, 2023)
This research employs action research using the Kemmis & McTaggart model. It consists of two cycles, each with four phases: 1) planning, 2) implementation, 3) observation, and 4) reflection. Each cycle consists of two meetings. The data collection methods used include observation, tests, and documentation. The results of the research obtained that, the application of audiovisual media in improving vocabulary mastery for seventh-grade students at Muhammadiyah Boarding School Valuvo can be implemented well. This is evidenced by the results of observing student learning activities during the lessons. In the first cycle, a score of 3 with a percentage of 75% was achieved, indicating weak competence, while in the second cycle, the score increased to 4 with a percentage of 81%, indicating good competence. This increase is observed from the students' responses, where all research indicators were well-implemented. The improvement in vocabulary mastery for seventh-grade students at Muhammadiyah Boarding School Valuvo before and after applying audiovisual media increases in each cycle. This is evident from the percentage of students who achieved the minimum completeness criteria score of 75. The average score before the cycle was 46.3 with a completion rate of 4%, indicating weak competence. In the first cycle, the average score increased to 71.5 with a completion rate of 48%, indicating acceptable competence. In the second cycle, the average score reached 96 with a completion rate of 100%, indicating excellent competence. ملخص البحث اهداف هذا البحث: (1) لمعرفة تطبيق المادة التعليمية القائمة على أساس الوسيلة السمعية البصرية VCD في ترقية إتقان المفردات في طلبة الصف السابع بالمدرسة الثانوية الداخلية محمّدية فالوفو. (2) لمعرفة إتقان الطالب المفردات قبل وبعد تطبيق المادة التعليمية القائمة على أساس الوسيلة السمعية البصرية VCD في طلبة الصف السابع بالمدرسة الثانوية الداخلية محمّدية فالوفو. يستخدم هذا البحث نوع البحث الاجراء بنموذج Kemmis & Mc Taggar. يتكون هذا البحث من دورتين ولكل دورة اربع مراحل وهي: 1) التخطيط، 2) التنفيذ، 3) الملاحظة، 4) الإنعكاس. كل دورة تتكون من اجتماعين. اسلوب جمع البيانات المستخدمة هي الملاحظة، والاختبار، والتوثيق. نتائج البحث التي تم الحصول عليها: (1) تطبيق الوسيلة السمعية البصرية في تحسين اتقان المفردات لطلبة الصف السابع بالمدرسة الثانوية الداخلية محمدية فالوفو يمكن تنفيذه بجيد. يتضح هذا من خلال نتائج مراقبة انشطة تعليم الطالب في اثناء التعليم. في الدورة الاولى تنال الدرجة 3 بنسبة مئوية ٪75 بالكفاءة ضعيف والدورة الثانية ترفع إلى 4 بنسبة مئوية ٪81 بالكفاءة جيد. ينظر هذه الزيادة من اجابات الطالب حيثما يتم تنفيذ كل مؤشرات البحث بجيد. (2) تحسين اتقان المفردات لطلبة الصف السابع بالمدرسة الثانوية الداخلية محمدية فالوفو قبل وبعد تطبيق الوسيلة السمعية البصرية يزيد في كل الدورة. يتضح هذا من خلال النسبة مئوية لطلبة الائي تمكن تحقيق الحد الادنى من درجة معايير الاكتمال يعنى 75. تنال الدرجة المتوسط في قبل الدورة 46،3 مع نسبة الاكتمال بلغت ٪4 بالكفاءة ضعيف. وتنال الدرجة المتوسط في الدورة الاول 71،5 مع نسبة الاكتمال ٪48 الكفاءة مقبول. وتنال الدرجة المتوسط في الدورة الثانية 96 مع نسبة الاكتمال بلغت ٪100 بالكفاءة ممتاز.